HUBUNGAN HIGIENITAS PERSONAL SISWA DENGAN KEJADIAN KECACINGAN NEMATODE USUS - Diah Lestari Lestari (Poltekkes Kemenkes Jakarta III, 2016)
Intestinal worm infection by nematode worms also referred to as the stomach, is a group of worms that are transmitted through the soil (soil-transmitted Helminths). Worm infection in children in Indonesia prevalence reached 60-80% . Many studies worm disease in children occur during primary school age. Important species that commonly infects humans are kind of Ascaris lumbricoides, Trichuris trichiura, Strongyloides stercoralis and hookworm (Ancillostoma duodenale and Necator americanus). Genesis worm disease on Primary School Children can occur by factors such as students' personal hygiene habits play on the ground, hand washing, use of footwear, sucking fingers, and the physical condition of the students. The research objective was to determine the relationship between personal hygiene students with the incidence of intestinal nematode worm infection. Design studies using cross-sectional study with a sample of 160 through primary data through interview, observation and the eggs and larvae of intestinal nematode worms in the stool with Kato- Katz method.The results showed significant relationship between hand washing habits in students with the incidence of worm infection (p value 0.033). The prevalens of infection in students of 57.5%, by worms A.lumbricoides 74.8% and 25.2% by T.trichiura, infection does not occur by hookworm.